Economic value and cost-effectiveness of biventricular versus right ventricular pacing: results from the BLOCK-HF study. (3rd October 2019) - Chung, Eugene S.; St. John Sutton, Martin G.; Mealing, Stuart; Sidhu, Manpreet K.; Padhiar, Amie; Tsintzos, Stelios I.; Lu, Xiaoxiao; Verhees, Koen J. P.; Lautenbach, Amy A.; Curtis, Anne B.
Abstract: Aims: The Biventricular vs Right Ventricular Pacing in Heart Failure Patients with Atrioventricular Block (BLOCK-HF) demonstrated that biventricular (BiV) pacing resulted in better clinical and structural outcomes compared to right ventricular (RV) pacing in patients with atrioventricular (AV) block and reduced left ventricular ejection fraction (LVEF; ≤50%). This study investigated the cost-effectiveness of BiV vs RV pacing in the patient population enrolled in the BLOCK-HF trial. Methods: All-cause mortality, New York Heart Association (NYHA) Class distribution over time, and NYHA-specific heart failure (HF)-related healthcare utilization rates were predicted using statistical models based on BLOCK-HF patient data. A proportion-in-state model calculated cost-effectiveness from the Medicare payer perspective. Results: The predicted patient survival was 6.78 years with RV and 7.52 years with BiV pacing, a 10.9% increase over lifetime. BiV pacing resulted in 0.41 more quality-adjusted life years (QALYs) compared to RV pacing, at an additional cost of $12, 537. The "base-case" incremental cost-effectiveness ratio (ICER) was $30, 860/QALY gained. Within the clinical sub-groups, the highest observed ICER was $43, 687 (NYHA Class I). Patients receiving combined BiV pacing and defibrillation (BiV-D) devices were projected to benefit more (0.84 years gained) than BiV pacemaker (BiV-P) recipients (0.49 years gained), compared to dual-chamber pacemakers. Conclusions: BiV pacing in AV block patients improves survival and attenuates HF progression compared to RV pacing. ICERs were consistently below the US acceptability threshold ($50, 000/QALY). From a US Medicare perspective, the additional up-front cost associated with offering BiV pacing to the BLOCK-HF patient population appears justified.